Assessment of women's needs and wishes regarding interprofessional guidance on oral health in pregnancy - a qualitative study - Merle Ebinghaus; Caroline Johanna Agricola; Janne Schmittinger; Nataliya Makarova; Birgit-Christiane Zyriax (BMC, 2024)
Abstract Background Poor oral and dental health due to oral dysbiosis during pregnancy increases the risk for negative pregnancy outcomes. Communicating the importance of oral health is therefore essential in reducing the risk of adverse pregnancy outcomes. Professional guidance could substantially support women's positive perception of their own competence. Information on oral health should be provided by healthcare professionals such as midwives, obstetricians and dentists. The aim of this study was to assess the needs, wishes and preferences of pregnant women in Germany, regarding interprofessional collaboration and guidance on oral health during pregnancy. Methods Sources of information, preferences regarding information supply as well as the need for interprofessional collaboration of involved healthcare professions were investigated in six online focus groups with pregnant women. In addition, three expert interviews with a midwife, an obstetrician and a dentist were conducted. The focus groups and interviews were analysed using qualitative content analysis according to Kuckartz. Results 25 pregnant women participated in focus groups. Pregnant women in all trimesters, aged 23 to 38 years, were included. Many women did not receive any or received insufficient information on oral health during pregnancy and wished for more consistent and written information from all involved healthcare providers. The extent of oral health counselling women received, heavily relied on their personal initiative and many would have appreciated learning about the scientific connection between oral health and pregnancy outcomes. An overall uncertainty about the timing and safety of a dental visit during pregnancy was identified. Interviews with experts provided additional insights into the working conditions of the involved healthcare professionals in counselling and emphasised the need for improved training on oral health during pregnancy in their respective professional education as well as thematic billing options in relation to this topic. Conclusion Guidance of women on oral health during pregnancy appears to be insufficient. Providing information adapted to the needs, wishes and preferences of women during pregnancy as well as the implementation of this topic in the education of involved healthcare professionals could contribute to an improved prenatal care for pregnant women and subsequently a reduced risk of negative pregnancy outcomes.